2020
DOI: 10.26740/al-uqud.v4n2.p250-267
|View full text |Cite
|
Sign up to set email alerts
|

The Malaysian Fund Managers Perspective on the Viability of Takaful Operators Investment

Abstract: Takaful operators are expected by the policyholders to act beyond the role of traditional insurance companies that only offer Shariah-compliant protection services. They are expected to be commercially viable. One of the ways to be commercially viable is takaful operators must be able to invest the policyholders' funds in the profitable investment avenues. Nevertheless, the critical issue before investing the funds is to develop products that are suitable with the takaful operators' investment strategy. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Long before this study, Salman & Htay (2012) have also introduced takaful-based waqf in India to reduce poverty and improve people's lives. Furthermore, Muhamat (2019) also explained the integration of waqf in takaful as a feature in takaful policy. It can be concluded that the waqf-takaful model also has sustainable potential for society.…”
Section: Resultsmentioning
confidence: 99%
“…Long before this study, Salman & Htay (2012) have also introduced takaful-based waqf in India to reduce poverty and improve people's lives. Furthermore, Muhamat (2019) also explained the integration of waqf in takaful as a feature in takaful policy. It can be concluded that the waqf-takaful model also has sustainable potential for society.…”
Section: Resultsmentioning
confidence: 99%